2021
DOI: 10.1038/s41598-021-85788-0
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics analysis reveals a modified amino acid metabolism that correlates with altered oxygen homeostasis in COVID-19 patients

Abstract: We identified the main changes in serum metabolites associated with severe (n = 46) and mild (n = 19) COVID-19 patients by gas chromatography coupled to mass spectrometry. The modified metabolic profiles were associated to an altered amino acid catabolism in hypoxic conditions. Noteworthy, three α-hydroxyl acids of amino acid origin increased with disease severity and correlated with altered oxygen saturation levels and clinical markers of lung damage. We hypothesize that the enzymatic conversion of α-keto-aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
108
2
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(133 citation statements)
references
References 58 publications
19
108
2
4
Order By: Relevance
“…Consistent with our study, also other metabolomics investigations found modification of aspartate, glutamate, alanine, phenylalanine, and arginine amino acid metabolism, revealing increased levels of aspartate, glutamate, phenylalanine, and a decline of serotonin along COVID-19 disease severity, as well as accumulation of succinic acid [18,41,42]. In the mitochondrion, succinic acid can be produced in the metabolic pathway of propionate through the breakdown of branched-chain amino acids, or the β-oxidation of odd-chain fatty acids and cholesterol degradation [43,44].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with our study, also other metabolomics investigations found modification of aspartate, glutamate, alanine, phenylalanine, and arginine amino acid metabolism, revealing increased levels of aspartate, glutamate, phenylalanine, and a decline of serotonin along COVID-19 disease severity, as well as accumulation of succinic acid [18,41,42]. In the mitochondrion, succinic acid can be produced in the metabolic pathway of propionate through the breakdown of branched-chain amino acids, or the β-oxidation of odd-chain fatty acids and cholesterol degradation [43,44].…”
Section: Discussionsupporting
confidence: 92%
“…What is more, ornithine and glutamate showed positive correlation with lactic acid, suggesting that these disturbances may be strictly interconnected with the overall damage induced by SARS-CoV-2 infection, in part including oxygen imbalance and tissue injury. Accordingly, increased levels of glutamic acid were found to positively correlate with anion gap values in severe COVID-19 [42]. Beside its role in the neurotransmission, an important immunomodulator function has been addressed to the glutamate, finding several glutamate receptors on the surface of T-cells and glutamate transporters in antigen presenting cells such as dendritic cells and macrophages [42,53].…”
Section: Discussionmentioning
confidence: 99%
“…Pàez-Franco et al, in a preprint study comparing healthy individuals with mild and severe patients, found that phenylalanine is one of the 15 metabolites that differentiate the healthy from mild and severe patients, while it is not among the discriminating when comparing mild to severe cases. Moreover, in this study, several amino acids decrease in the mild patients compared to the controls (methionine, glutamine, threonine, isoleucine, and leucine) [ 59 ].…”
Section: Breast Milk Sars-cov-2 and Metabolomicsmentioning
confidence: 95%
“…Unfortunately, the necessary prevention and treatment strategies of COVID-19 have led to restriction measures that are hampering the routine care of common chronic metabolic conditions like hypercholesterolemia, hypertension, hyperglycemia (diabetes), and obesity [ 1 ]. It is of particular concern that during the acute phase of COVID-19, the control of pre-existing metabolic diseases tends to get worse which again increases the risk for complications and a poor outcome in these patients [ [2] , [3] , [4] ]. A significant contributor to these complications is endothelial dysfunction which is associated with COVID-19 [ 5 ].…”
Section: The Bidirectional Connection Between Covid-19 and Metabolic Diseasesmentioning
confidence: 99%